Leonardo Coimbra's line of thought: Creationism - Rodrigues , João Bartolomeu (2022)
Inserted in a time of constant change, Leonardo Coimbra marked the Portuguese history through his active role in the cultural field. The Creationism, name attributed to the line of thoughts that he followed, was based on freedom of thought and choice, following the uncertain and the variable opinions of the period in which he acted. He was also part of remarkable projects that marked the first phase of the Modernism movement, as well as the Renascença Portuguesa, of which he was one of the founders.